Problem Solving and Personality in Security Officers - Halim İşsever; Elif Ezirmik; Nefise Şeker; Zeynep Betül Sağlam; Gözde Öztan; Fatma Canatar (Journal of Economy Culture and Society)
The study was conducted to examine the relationship between problem solving skills and personality traits of university security guards. The research was carried out with 190 security personnel working at universities in 2019. In the study, the Problem- Solving Skills Scale for Adults and the Big Five Personality Questionnaire-50 Turkish Form were used. 83.7% of the participants in the study were male, 73.2% were married, 68.4% were high school graduates, and 95.8% had in-service training. According to the logistic regression model, the results of our study were as follows: the problem solving skill ‘Considering the Effects of the Solution of the Problem’ was OR= 2.33 times (95% CI: 1.028-5.29) higher in female security guards than in males; ‘Problem- Solving Through Modeling’ was OR=0.48 times (95% CI : 0.237-0.987) higher in single security guards than married ones; and OR=2.18 times (95%CI: 1.181-4.047) higher in ones whose ‘responsibility’ personality trait was above the median value. The problem- solving skills of the security personnel were found to be related to their personality traits, gender, marital status, working time and education level.